The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ma15238487
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Multiple Mechanical Recycling of Particleboards on Their Selected Mechanical and Physical Properties

Abstract: This is a bridge between circular economy issues and wood-based panels technology, especially particleboards. Because these composites contain a significant amount of non-wood raw material (10–12% thermoset resin, high hardness laminates, among others), their mechanical recycling leads to an uncontrollable reduction in produced particle size. This problem can be especially significant since the particleboards can be intended for multiple recycling due to the shortening of their service life. This research aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…As a result, the new board will have lower performance in all properties. These results are in line with the findings of other studies [ 18 ].…”
Section: Results–discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…As a result, the new board will have lower performance in all properties. These results are in line with the findings of other studies [ 18 ].…”
Section: Results–discussionsupporting
confidence: 94%
“…The recycling of particleboard with wood chips is a topic that has been studied by various scientists. New recycled wood-based panels have been produced on a laboratory scale, and their properties have been studied [ 16 , 17 , 18 , 19 ]. However, no literature references were found on the recycling of panels based on hemp shives, such as those produced in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…The size of the dust particles remained lower than 0.125 mm, and the bulk density equaled about 270 kg m −3 . The entire procedure and characteristics have been described in [39]. Other studies have confirmed that processing a wood composite made from already fragmented wood contributes to the formation of smaller fractions compared to the processing of solid wood [40].…”
Section: Methodsmentioning
confidence: 99%
“…The global production of particleboard increased by 61.7% from 64.3 million m 3 in 2000 to 104 million m 3 in 2021, and the growth is expected to continue rising [4]. A large variety of lignocellulose-based resources serve as raw materials, such as wood, natural fibers, forest-based and agro-industrial side-streams and residues, and recycled wood [5][6][7]. Research on particleboards is now focused on finding homogenous non-wood feedstock and bio-based adhesives with low environmental impact [1].…”
Section: Introductionmentioning
confidence: 99%